Social enterprise as a strategy to advance patient-oriented health services innovation: learning from the Alberta Family Integrated Care model - Shahid, Anmol; Graham, Kristen; Benzies, Karen (Frontiers in Health Services, 2025)
This community case study outlines the conceptualization, development, implementation, and commercialization of the Alberta Family Integrated Care (Alberta FICare) model, offering insights into a unique way of sustaining patient-oriented innovations through social enterprise. Our team developed the Alberta FICare model to include families as partners in care in neonatal intensive care units (NICUs). Research phases of our model showed improved outcomes for neonates (shorter hospital stays), their families (greater caregiving self-efficacy, reduced psychosocial distress), and the health system (cost avoidance). Despite co-development of the model with families, providers, and leaders, rigorous testing (cluster randomized controlled trial), and province-wide scale-up (now standard of care in all 14 Alberta NICUs) efforts to sustain the model stalled due to shifting health system priorities. To address this challenge, we incorporated a social enterprise (Liminality Innovations Inc.) to sustain the model of care and support broader dissemination of family integrated care practices in NICUs beyond Alberta. While this strategy fostered sustainment and growth of our model, it also raised challenges. Some of these challenges included tackling perceptions within the research and practice communities that commercialization undermines research integrity. We share our experiences to highlight the potential of ethical, mission-driven commercialization through social enterprise to support innovation in learning health systems through ongoing interest holder engagement, responsible stewardship, and improving learning health system outcomes as the central goal.